Association of polymorphism c.‐124G>A and c.‐16 C>T in the promoter region of human INHA gene with altered sperm parameters; A pilot study. Issue 10 (27th August 2020) - Rafaqat, Wardah; Kayani, Muhammad Rohan; Fatima, Tasneem; Shaharyar, Saeeda; Khan, Shagufta; Ashraf, Mussarat; Afzal, Usman; Rehman, Rehana
Abstract: Objective: The objective of this was to demonstrate the association of Inhibin α ( INHα ) c.‐124G>A and INHα ‐ c.‐16 C>T polymorphisms with altered sperm parameters in a selected male population of Karachi, Pakistan. Study Design & Settings: In this pilot study, male subjects were stratified on the basis of the WHO criteria for altered sperm parameters; 83 (cases—altered sperm parameters) and 30 (controls—normal sperm parameters) subjects were included for analysis of INHα‐c.124G>A polymorphism and 88 (cases) and 38 (controls) were analysed for INHα ‐c‐16 C>T polymorphism. Genotyping of INHα‐c.‐124G>A and INHα‐c.‐16 C>T was performed by PCR‐RFLP, genotype distribution in Hardy‐Weinberg equilibrium was evaluated by binary logistic regression model. Results: For the c.‐124G>A polymorphism in INHα gene, frequency of the three major genotypes in controls was: GG: 80.0%, GA: 20.0% and AA: 0% and in cases was: GG: 59.0%, GA: 30.2% and AA: 10.8%. The GG genotype was significantly associated with male infertility ( P < .045, OR = 2.776, 95% CI = 1.025‐7.513) while the GA genotype was not significantly associated with infertility ( P < .290 OR = 0.580, 95% CI = 0.211‐1.593). Frequency of mutant AA genotype was 10.8% in cases (altered sperm parameters) and absent (0%) in normal sperm parameter (controls). The frequencies of three major genotypes CC, CT and TT did not show any significant difference between cases and controls ( P > .05). Conclusion: The results from our study exhibited a significant association of c.‐124G>A polymorphism in the INHα gene promoter region with male infertility in the Pakistani population. A significant association of c.‐16 C>T polymorphism with male infertility, however, was not observed. Further large‐scale studies should be conducted to confirm this association.